When to use probiotics in luminal gastrointestinal disorders?. Issue 5 (September 2020) - Elangovan, Abbinaya; Fischer, Monika
Abstract : Purpose of review: With the growing popularity and commercialization of probiotics, it is important to understand the implications of existing randomized controlled trials and their applicability in the clinical setting to treat luminal gastrointestinal diseases. Recent findings: Probiotics may be useful in the prevention of antibiotic-associated diarrhea, prevention of Clostridioides difficile infection and eradication of Helicobacter pylori . Some evidence supports the use of probiotics in the treatment of ulcerative colitis, prevention and treatment of pouchitis and irritable bowel syndrome. Caution has to be exercised in immunocompromised and critically ill individuals. New society guidelines do not encourage probiotic use in gastrointestinal disorders with the exception of premature infants to prevent necrotizing enterocolitis. Summary: Despite burgeoning body of literature and wide acceptance by the public, a thorough understanding of efficacy and safety of probiotics is lacking. Uniform dosage, standardized clinical end points, personalization based on host microbial profile and longer duration of follow-up on the research front may help in the future in appropriate positioning of probiotics in health and disease.